Project-Based Learning Sebagai Inovasi Pedagogik Pembelajaran Fikih: Kajian Literatur Terhadap Efektivitas dan Penerapannya - Siska Nirmala; Sholikah Sholikah (Muróbbî: Jurnal Ilmu Pendidikan, 2026)
Project-Based Learning (PjBL) has emerged as an innovative pedagogical model that emphasizes active student participation, authentic problem-solving, and the integration of knowledge through project-based tasks. Within the context of Islamic education, particularly in Fiqh learning, PjBL offers a transformative approach to bridging theoretical understanding and practical application of Islamic jurisprudence. This review study aims to analyze previous research findings on the effectiveness of PjBL in Fiqh instruction compared to conventional teaching methods. Employing a systematic literature review approach, relevant studies published between 2015 and 2025 were examined to identify patterns, challenges, and outcomes associated with the implementation of PjBL in Islamic educational institutions. The findings indicate that PjBL contributes significantly to improving students’ conceptual comprehension, critical thinking skills, and religious character formation. However, its effectiveness is influenced by contextual factors such as teacher competence, curriculum integration, and institutional support. This study concludes that PjBL serves as a pedagogical innovation capable of fostering holistic learning in Fiqh education while promoting 21st-century competencies and spiritual values.